What are the current practices of sports physiotherapists in integrating psychological strategies during athletes' return-to-play rehabilitation? Mixed methods systematic review. (July 2019) - Annear, Andrew; Sole, Gisela; Devan, Hemakumar
Abstract: Objective: The primary aim was to identify the current practices of sports physiotherapists in implementing psychological strategies during athletes' return-to-play rehabilitation and, secondly, to explore their attitudes and challenges to do so. Methods: An electronic search of the PubMed, CINAHL, Scopus, Medline, Google Scholar, Cochrane Library, AMED, and PsycINFO databases was performed. Studies were considered eligible if they explored physiotherapists' implementation of psychological strategies during athletic rehabilitation. Methodological quality of included studies was assessed using the Guidelines for Critical Review Form. Data were synthesised using thematic analysis. Results and conclusions: Eleven studies involving 1440 sports physiotherapists were included: six were quantitative, three were qualitative, and two were mixed-method studies. Most sports physiotherapists recognised the importance of implementing psychological strategies during athletes' rehabilitation but were unsure whether it is within their scope. Common psychological strategies implemented included goal setting and encouraging positive self-thoughts. Barriers to implementing psychological strategies include lack of knowledge and training at undergraduate level, lack of postgraduate psychology courses available, and perceived stigma from athletes toward seeking psychological support. Strategies for sports physiotherapists to incorporate psychological strategies during athletes' return-to-play rehabilitation could include targeted professional development opportunities to gain confidence in implementing psychological strategies. Highlights: Sports physiotherapists commonly use goal setting and positive self-thoughts. Importance of psychological strategies throughout rehabilitation is recognised. Sports physiotherapists have limited training in psychological strategies. Targeted professional development opportunities are required to maximise confidence.